From the Iowa Birdline, December 1, 1991-February 15, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Summary of the Iowa Birdline update for December 1, 1991-February 15, 1992. Highlights of the update include sightings of a Marbled Murrelet, Prairie Falcons, a Pine Warbler, Northern Saw-whet Owls, and Common Redpolls. Also of note were the unusual species of gulls that were present from mid-December through mid-February. Epson - sheet feed